Evaluation the Quality of Health Services Based on SERVQUAL Model in Ahwaz Health Care Centers, Iran - Seyyed Mansour Kashf; Diba raufi; Tayebeh Rakhshani; Hasan Hashemi (Caspian Journal of Health Research, 2019)
Background: Service quality is one of the main challenges in health systems. In quality management, service recipients play an important role in identifying their needs and preferences. The present study was carried out to evaluate the quality of health services provided in health centers of Ahvaz city based on the SERVQUAL model in 2016. Methods: This cross-sectional descriptive study was conducted on 384 person referred to the health centers in the west of Ahvaz city in 2016. The sample were selected through quota sampling method. The SERVQUAL questionnaire which measures the five dimensions of Tangibles, Reliability, Responsiveness, Assurance and Empathy in service delivery was applied to collect the required data. The data were analyzed using paired t-test. Results: In general, there were differences between perception and expectation of the five service dimensions and the differences were negative (expectations were beyond perceptions). The mean total difference of service quality was -0.68 (P-value < 0.05). The lowest and the highest mean scores of quality difference were obtained for reliability (-0.53) and empathy (-1.04) dimensions, (P-value < 0.001). Conclusion: This study revealed negative differences in all five service dimensions. So, promotion and evaluation of service quality should be continuously considered in planning. Since the highest difference in service quality was observed in empathy dimension, it seems essential to hold customer service training courses for increasing communication skills for employees